Gramsci, filologo - Bianchi, Alvaro (International Gramsci Journal, 2023)
With this in view it goes into the philological debates that were taking place in Italy after the formation of the new national state. The article reconstructs Gramsci’s intellectual formation at the Faculty of Letters and Philosophy at the University of Turin, particular attention being paid to his studies in glottology and philology. After this, the article concentrates its attention on two aspects of Gramsci’s intellectual production: there is a first moment, before his imprisonment, in which philology is a weapon for cultural polemics, mainly against the supporters of Italian nationalism; and a second moment, in prison, when philology becomes the constitutive element of a historical method of research and of the philosophy of praxis itself.